Determinação e avaliação de riscos de metais pesados no solo de um "lixão" desativado no município de Francisco Beltrão - Paraná - Souza, Vinicius Baldo de (2019)
Incorrect disposal of solid waste negatively influences the quality of life of the population and damages the environment. Many of the materials disposed of in an improper location have potentially toxic and hazardous elements. Heavy metals have significant polluting potential because of their ability to alter soil characteristics and contaminate other environmental compartments by migration or mobilization under certain conditions. The present work aims to evaluate the possible risks of the Água Branca neighborhood dump, in the municipality of Francisco Beltrão - PR, which received municipal solid waste for over fifteen years and was deactivated eighteen years ago. It is located in the Marrecas river basin, upstream of the municipality's water catchment. The soil was characterized by physical and chemical tests, emphasizing the analysis of metals aluminum (Al) iron (Fe), copper (Cu), manganese (Mn) and zinc (Zn). From the results found and with the help of geostatistics t was possible to determine the presence of these metals in the area of influence of the dump. Mn and Zn concentrations (mean 545.27 mg.kg-1 and 21.86 mg.kg-1 in this order) were found to be relatively higher than in the reference soil (average 185 mg.kg-1 and 3.85 mg.kg-1 for Mn and Zn respectively), indicating possible contamination. The present work is expected to contribute to the monitoring of the deactivated dump activity and provide future research to assist decision making regarding the recovery of the degraded area.